Объяснение:
0\hfill\\x-3>0\hfill\\x-3\ne1\hfill\\\end{gathered}\right.\Leftrightarrow\left\{\begin{gathered}x>-1\hfill\\x>3\hfill\\x\ne4\hfill\\\end{gathered}\right.\hfill\\\boxed{x\in(3;+\infty)}\hfill\\\end{gathered}\]" class="latex-formula" id="TexFormula2" src="https://tex.z-dn.net/?f=%5C%5B%5Cbegin%7Bgathered%7D2%29%5C%3B%5C%3B%7B%5Clog_%7Bx-3%7D%7D%28x%2B1%29%5Chfill%5C%5C%5Cleft%5C%7B%5Cbegin%7Bgathered%7Dx%2B1%3E0%5Chfill%5C%5Cx-3%3E0%5Chfill%5C%5Cx-3%5Cne1%5Chfill%5C%5C%5Cend%7Bgathered%7D%5Cright.%5CLeftrightarrow%5Cleft%5C%7B%5Cbegin%7Bgathered%7Dx%3E-1%5Chfill%5C%5Cx%3E3%5Chfill%5C%5Cx%5Cne4%5Chfill%5C%5C%5Cend%7Bgathered%7D%5Cright.%5Chfill%5C%5C%5Cboxed%7Bx%5Cin%283%3B%2B%5Cinfty%29%7D%5Chfill%5C%5C%5Cend%7Bgathered%7D%5C%5D" title="\[\begin{gathered}2)\;\;{\log_{x-3}}(x+1)\hfill\\\left\{\begin{gathered}x+1>0\hfill\\x-3>0\hfill\\x-3\ne1\hfill\\\end{gathered}\right.\Leftrightarrow\left\{\begin{gathered}x>-1\hfill\\x>3\hfill\\x\ne4\hfill\\\end{gathered}\right.\hfill\\\boxed{x\in(3;+\infty)}\hfill\\\end{gathered}\]">
(y-2)^2; (y+2)^2
(7x-3)^2; (7x+3)^2
(8m^3-7)^2; (8m^3+7)^2
(-6-10p)^2; (-6+10p)^2
(2x-3y)^2; (2x+3y)^2
(5e-4q)^2; (5e+4q)^2
(9t+3z)^2 (это квадрат разности!); (9t-3z)^2 (это квадрат суммы!)
(2d+5d)^2 = (7d)^2 (разности!); (2d-5d)^2 = (-3d)^2 = (3d)^2 (суммы!)
2)
72^2 = (70 + 2)^2 = 70^2 + 2*70*2 + 2^2 = 4900+280+4 = 5184
31^2 = (30+1)^2 = 30^2 + 2*30*1 + 1^2 = 900 + 60 + 1 = 961
3,2^2 = (3 + 0,2)^2 = 3^2 + 2*3*0,2 + 0,2^2 = 9 + 1,2 + 0,04 = 10,24
6,3^2 = (6 + 0,3)^2 = 6^2 + 2*6*0,3 + 0,3^2 = 36+3,6+0,09 = 39,69
2,95^2 = (3-0,05)^2 = 3^2-2*3*0,05+0,05^2 = 9-0,3+0,0025 = 8,7025
9,99^2=(10-0,01)^2=10^2-2*10*0,01+0,0001=100-0,2+0,0001=99,8001